Assisted network governance: an inclusive innovation to mitigate extreme water scarcity - Gutiérrez, Denise; Glückler, Johannes (Global environmental change, 2022)
We study a local innovation of natural resource governance in Chile in times of extreme water scarcity. Through the issuance of a scarcity decree, the government obliges local water user associations (WUAs) to reach viable water redistribution agreements in order to avoid being overruled by the state. In the Aconcagua River, the government together with the WUAs created the Executive Committee, where only the WUAs have a vote, but private and public stakeholders participate in the process of negotiating water use agreements. Grounded on thematic coding of the detailed minutes of over 80 committee meetings since its inception, we examine the workings of a new local model of Assisted Network Governance (ANG). Based on content and social network analysis of over 1,000 directed interactions among committee members, we find that ANG, as an element of broader hybrid governance, has not only produced viable agreements for immediate water redistribution, but has also facilitated longer-term system improvements by building mutual understanding, resolving conflicts, and mobilizing external resources to improve infrastructure. We conclude that ANG helps accomplish common objectives in the field of natural resources under conditions of extreme water scarcity.
Gesehen am 22.09.2022